Multikulturalisme dan Kebijakan Publik: Rekognisi dan Perlindungan Hak Asasi Masyarakat Adat di Indonesia dalam Perspektif Universalisme Interaktif Seyla Benhabib - Sentana, Fajar Yudha; Manalu, Abby Gina Boang (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2023)
This article discusses the issue of recognition and protection of community rights in Indonesia in the light of Seyla Benhabib's interactive universalism. The research aims to analyse the challenges and opportunities in pursuing recognition and protection of indigenous peoples within the framework of interactive universalism, by emphasising cultural diversity and the importance of the local context. Interactive universalism concerns about the importance of dialogue, public participation, and the adaptation of democratic principles in preserving indigenous peoples' rights. Here interactive universalism is used to review the state of indigenous peoples' rights in Indonesia. Various public policies have caused conflicts, ranging from land take over to human rights violation, that are detrimental to the existence of indigenous peoples. Public policy as a representation of the state should protect their rights. In this article public policies are reviewed from the perspective of interactive universalism. The review process will consider cultural diversity in order to prevent future problems and to recommend adequate and assured protection of the rights of indigenous peoples. This research is a qualitative research using a philosophical approach and literature review to analyse actual problems.